Pelatihan Microsoft Office kepada Remaja di Desa Kindang - Hartini Hartini; Eka Apriyanti; Hasria Alang (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2022)
This community service activity is carried out to foster knowledge an understanding for teenagers to improve basic Microsoft Office computer skills, especially the use of Microsoft Word, Microsoft Excel, and Microsoft Power Point. This training activity was carried out for 2 weeks, starting from the stages of lectures, questions and answers, and direct practice independently. The target group that participates in the activity is youth with middle and high school age. The number of participants who attended was 22 participants who were divided into 2 groups. From this activity, this teenager has been able to master Microsoft Office, especially Microsoft Word, Microsoft Excel, and Microsoft Power Point, so that they are proficient in using both software to do school assignments and as a provision for work later. The final result of this activity is in the form of writing in the form of publication of scientific articles.